Incidence of late occurring bradyarrhythmias after TAVI with the self-expanding CoreValve® aortic bioprosthesis - Chorianopoulos, Emmanuel; Krumsdorf, Ulrike; Pleger, Sven Torsten; Katus, Hugo; Bekeredjian, Raffi (Clinical research in cardiology, 2012)
ObjectivesAnalysis of timing, type, electrocardiographic and patient characteristics of postinterventional bradyarrhythmias after CoreValve implantation.BackgroundTranscatheter aortic valve implantation (TAVI) has become an accepted alternative to surgical therapy in patients with high risk. Among the major drawbacks of this procedure is the need for postprocedural permanent pacemaker implantation (PPM). Although predictors for the postinterventional need for PPM are increasingly recognized, thresholds and rates may vary between centers.MethodsWe conducted a retrospective single-center analysis in 130 consecutive patients with successful transfemoral CoreValve implantation without preexisting pacemaker implants.ResultsPostprocedural bradyarrhythmias occurred in 36.2% post-TAVI. Compared to those without postinterventional bradyarrhythmias, these patients had longer preprocedural PR intervals (P = 0.012), broader QRS-complexes (P = 0.001) and prolonged QTc intervals (P = 0.001). Patients with postinterventional bradyarrhythmias had significantly more often preprocedural RBBB (35.2 vs. 14.1%; P = 0.0059). In contrast, no difference was observed with respect to annulus/prosthesis ratio or the use of the large 29-mm prosthesis. The vast majority of patients developed bradyarrhythmias directly after CoreValve implantation or within the first 48 h thereafter. However, 7.6% developed significant bradyarrhythmia more than 48 h after TAVI, and 3.8% of the whole cohort developed significant bradyarrhythmias even >96 h after TAVI. One patient died at day 5 post-TAVI due to asystole.ConclusionsLate occurrence of bradyarrhythmias should be recognized as a significant contributor to postprocedural outcome after TAVI. Although this is a well known phenomenon after surgical valve replacement, it is less recognized after TAVI.